Cross-Border Effects of Fiscal Policies - Maleček, Petr, 1983-; Kadeřábková, Božena; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
This study seeks to analyse and quantify cross-border effects of discretionary fiscal policies from two major points of view. The aggregate approach rests on the use of the structural vector autoregression model (SVAR) and its extension, the global vector autoregression model (GVAR). The discretionary fiscal impulse itself is then defined as a change in cyclically adjusted balance of the government sector, calculated at quarterly frequencies. This section is then complemented by a case study of a single measure: the German car scrapping scheme during 2009 and its effects on the Czech economy. It was found that cross-border effects of discretionary fiscal policies may be indeed present, in case certain conditions are met. Importantly, a fiscal impulse has to originate from a sufficiently large economy and there needs to be a tight trade linkage between examined countries. In most cases, cross-border effects have also been found of lesser magnitude than direct impacts of fiscal policies on the domestic country. Finally, as demonstrated on the German-Czech case, even a single fiscal measure can trigger substantial cross-border spillovers. It was estimated that this measure positively contributed to real GDP growth in 2009 in the Czech Republic by 0.44 pp.
Vedoucí práce: Božena Kadeřábková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: obecná ekonomická teorie a dějiny ekonomických teorií [obor disert. práce]; disertace; dissertations